Enhanced helium ion irradiation tolerance in a Fe-Co-Ni-Cr-Al-Ti high-entropy alloy with L12 nanoparticles. (20th April 2023) - Zhao, Y.L.; Meng, F.L.; Yang, T.; Luan, J.H.; Liu, S.F.; Yeli, G.M.; Lin, W.T.; Liu, W.H.; Liu, X.J.; Liu, C.T.; Kai, J.J.
Highlights: Helium bubbles and large stacking faulted loops are observed as the dominant structural damage in the He ion irradiated HEA reinforced by L12 nanoparticles. The L12 nanoparticles provide numerous interfaces for He entrapment and damage elimination, which suppresses He bubble growth. A correlative TEM/APT characterization reveals that the RIS around He bubbles is dominated by the inverse Kirkendall mechanism. Irradiation-induced dissolution and re-precipitation of the L12 nanoparticles can retain the main microstructure of the L12 -strengthened HEA and provide a sustainable irradiation resistance. Abstract: L12 -strengthened high entropy alloys (HEAs) with excellent room and high-temperature mechanical properties have been proposed as promising candidates as structural materials for advanced nuclear systems. However, knowledge about their radiation response is fairly limited. In the present work, a novel HEA with a high density of L12 nanoparticles was irradiated with He ion at 500 °C. Transmission electron microscope (TEM) and atom probe tomography (APT) were employed to study the evolution of microstructural stability and radiation-induced segregation. Similar to the single-phase FeCoNiCr HEA, the main microstructural features were numerous large faulted dislocation loops and helium bubbles. While the irradiation resistance of the present L12 -strengthened HEA is much improved in terms of reduced bubble size, which could be attributed to the considerable He trapping efficiency of the coherent precipitate/matrix interface and the enhanced capability of the interface for damage elimination when the matrix channel width is narrow. APT analysis revealed that an inverse-Kirkendall-mechanism-dominated radiation-induced segregation (RIS) occurs around bubbles, where a significant Co enrichment and Ni depletion can be clearly observed. In addition, the competing dynamics of ballistic mixing and elemental clustering that raised from the irradiation-enhanced diffusion in a highly supersaturated matrix, along with the low precipitation nucleation barrier due to the small lattice misfit, lead to a dynamical precipitation dissolution and re-precipitation appears under irradiation. Such a promising phenomenon is expected to promote a potential self-healing effect and could in turn provide a sustainable irradiation tolerance over the operational lifetime of a reactor.